The Thromboembolism and Bleeding Event in Patients Receiving Warfarin, Dabigatran, or Rivaroxaban in Nonvalvular Atrial Fibrillation - Nor Hazirah B; Siti Nuraidah M; Mahfuzah I; Nur Amal Liyana O; Nurul Aiman Z; Nor Syafiqah AM (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Increasing in trend of Dabigatran and Rivaroxaban usage every year in Hospital Sultanah Nur Zahirah (HSNZ) has raised concerns regarding their effectiveness and safety compared to Warfarin. Therefore, we investigated the prevalence of thromboembolism (stroke or systemic embolism) and bleeding events in patients receiving Warfarin, Dabigatran or Rivaroxaban in our setting. This retrospective cohort study involved patients with nonvalvular atrial fibrillation who were started on Warfarin, Dabigatran or Rivaroxaban from January 1, 2014 to December 31, 2018. To fulfil inclusion criteria, patients must be on treatment for at least one year and for Warfarin group, at least 65% of Time in Therapeutic Range (TTR) should be achieved. Data were collected from Warfarin registration book, drug usage record card and Hospital Information System. 142 patients (Warfarin, n=98; Dabigatran, n=30; Rivaroxaban, n=14) with mean age of 68±8.7 years old were included in the study. Majority of them were male, Malay and non-smoker with 57.0%, 97.2% and 95.8% respectively. Upon study enrolment, all patients were at moderate risk of stroke (median CHA2DS2-VASc score=3) and low risk of bleeding (median HAS-BLED score=2). One Ischemic stroke was identified in each group of Rivaroxaban 15 mg and Dabigatran 150 mg. Four bleeding events occurred in all groups except for Dabigatran group that were hematuria, gum bleeding and upper gastrointestinal bleeding. Thromboembolism and bleeding events still occur in all groups. However, the prevalence is small in our setting with the percentage of 1.4% and 2.8% respectively. The events mostly attributed by the predisposed risk factors.